“RAYA AND THE LAST DRAGON” ANIMATION FILM: A SOURCE OF INSPIRATION FOR THE DEVELOPMENT OF INDONESIA'S CULTURE-BASED CREATIVE INDUSTRY - Yono, Sri; Satiyoko, Yohanes Adhi; Sumiyardana, Kustri; Wibowo, Eko Cahyo Kusumo; Suwondo, Tirto (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2024)
The success of the animated film